Beta-Glucan From Barley Attenuates Post-prandial Glycemic Response by Inhibiting the Activities of Glucose Transporters but Not Intestinal Brush Border Enzymes and Amylolysis of Starch - Malunga, Lovemore Nkhata; Ames, Nancy; Zhouyao, Haonan; Blewett, Heather; Thandapilly, Sijo Joseph (Frontiers in Nutrition, 2021)
Beta (β)-glucan (BG) from cereal grains is associated with lowering post-prandial blood glucose but the precise mechanism is not well elucidated. The main aim of this study was to understand the mechanism through which BG from barley affects post-prandial glycemic response. Waffles containing 0, 1, 2 and 3g barley BG and the same amount of available carbohydrate (15 g) were fed to the TIM-1 dynamic gastrointestinal digestion system to study the effect of BG on starch hydrolysis. Intestinal acetone powder and Xenopus laevis oocytes were used to study BG’s effect on mammalian intestinal 𝛼-glucosidase and glucose transporters. The presence of BG did not significantly affect the in vitro starch digestion profiles of waffles suggesting that BG does not affect α-amylase activity. Intestinal α-glucosidase and glucose transport activities were significantly (p < 0.0001) inhibited in the presence of barley BG. Interestingly, BG viscosity did not influence α-amylase, α-glucosidase, GLUT2 and SGLT1 activities. This study provides the first evidence for the mechanism by which BG from barley attenuates post-prandial glycemic response is via alteration of α-glucosidase, GLUT2 and SGLT1 activity, but not amylolysis of starch. The decrease in post-prandial blood glucose in the presence of BG is likely a consequence of the interaction between BG and membrane active proteins (brush border enzymes and glucose transporters) as opposed to the commonly held hypothesis that increased viscosity caused by BG inhibits starch digestion.